Qualidade dos medicamentos contendo dipirona encontrados nas residências de Araraquara e sua relação com a atenção farmacêutica - Serafim, Eliana Ometto Pavan [UNESP]; Del Vecchio, Adriana [UNESP]; Gomes, Juliana [UNESP]; Miranda, Aline [UNESP]; Moreno, Andréia de Haro [UNESP]; Loffredo, Leonor Monteiro de Castro [UNESP]; Salgado, Hérida Regina Nunes [UNESP]; Chung, Chin Man [UNESP] (FapUNIFESP (SciELO), 2007)
Many studies had described the morbi-mortality related to medicines. As for the strategies to reduce the possible risks for medicine therapy is very important to readvise the pharmaceutical activity, once the pharmacist has potential for constitute an essential part for the solution of problems related to the utilization of medicines. The purpose of this work was to demonstrate that the therapeutic subdosage and the microbiological contamination may be directly involved with the inappropriate manipulation of medicines stored in residences. Liquid dosage forms containing dipyrone market in Brazil and stored at homes in Araraquara (SP) were analyzed regarding quantitative and microbiological analysis. Only in 57% from 128 samples analyzed the drug quantity was in accordance. Moreover, 26.2% from 128 samples analyzed presented S. aureus, E. coli and Salmonella sp. These results demonstrated clear reduction in their quality, as well as the presence of molds and/or bacteria in some medicines that still agreed with the expirations dates, showing the importance of the pharmacist in advising the correct use and store of medicines.
Analysis of medicines and the relationship with pharmaceutical care: Quantitative and microbiological determination of medicines containing dipyrone
Keywords: Araraquara; Dipyrone; Pharmaceutical care; Stability; anador; baralgin; dipigina; dipimax; dipiron; dipyrone; dorona; dorspan; lisador; maxiliv; neosaldina; nofebrin; novalgina; sedalo composto; unclassified drug; adult; aged; controlled study; drug determination; drug dosage form; drug quality; drug storage; expiration date; female; human; male; microbial contamination; pharmaceutical care; pharmacist